Bioremediation of Mercury (II) Contaminated Seawater Using the Diatom Skeletonema costatum - Soedarti, Thin; S., Tini; H., Sucipto; Kuncoro, Eko P. (KnE Life Sciences, 2017)
The mercury contaminated seawater can pollute fish pond. Bioremediation is an effective process for the removal and recovery of mercury (II) from seawater using organism as an agent of biological degradation. The aim of this study was to know the optimum contact time and concentrations of the Skeletonema costatum cell inoculation on the bioremediation in mercury (II) contaminated seawater. This study has used the concentrations of the cell inoculation (5000; 10000; and 15000 cells/mL), the mercury (II) (0; 0.5; 1; and 2 mg/L), the contact time (24, 48, 72, 96, and 120 hours), and its replicated five times. The maximum bioremediation capacity of mercury (II) was 2 mg/L at 15 000 cells/mL and contact time 96 hours, with bioremediation efficiency 86.83%. Diatom Skeletonema costatum was efficient at removing 2 mg/L mercury (II) 79.5% for 5 000 cells/L at 72 hours, 83.3 % for 10 000 cells/L at 72 hours and 85% for 15 000 cells/L at 72 hours. The optimum contact time and concentrations of the Skeletonema costatum cell inoculation on the bioremediation in mercury (II) contaminated seawater for 2 mg/L, i.e. 5 000 cells/L for 72 hours (79.5%) Keywords: bioremediation; mercury (II); seawater; Skeletonema costatum.